Aerobic and anaerobic energy output in children - Mácek, M; Mácková, J (Sbornik lekarsky, 1994)
The adaptation of children to the exercise is discussed. The principles of adaptation are in children different of those of adults. The anaerobic metabolism of carbohydrates has lower activity and lower levels of LA by the lack of rate limiting enzyme phosphofructokinase and by earlier and higher increase of oxygen consumption in prepubertal children. The a-v O difference is higher in children; this contributes to perfection of the adaptation pattern of the cardiorespiratory system. Local flow in peripheral circulation in the working muscle is higher by 30% in children than in adults.
Keywords: laktáty; Glycerol; kyselina mléčná; cvičení; mladiství; mechanika dýchání; Lactic Acid; mužské pohlaví; Muscle, Skeletal; dítě; Child; věkové faktory; ženské pohlaví; Humans; Lactates; Hemodynamics; Catecholamines; kosterní svaly; hemodynamika; Respiratory Mechanics; glycerol; Age Factors; Exercise; Female; katecholaminy; Adolescent; lidé; Male